Scientific and innovative potential of the faculty of history of the Belarusian State University: traditions and modernity - Kakhanouski, Aliaksandr G. (Journal of the Belarusian State University. History, 2024)
A retrospective analysis of the formation of university historical science on the example of the Belarusian State University is presented. The significant contribution of the Belarusian State University scientists to the complex process of institutionalisation of Belarusian historical science is shown. It was emphasised that the formation of history in the republic and the definition of priorities in the organisation of scientific research were largely determined by the needs of the development of the state. It was noted that the most significant collective scientific publications on the history of Belarus were created thanks to the cooperation of specialists from the faculty of history of the Belarusian State University and the Institute of History of the National Academy of Sciences of Belarus. It is pointed out that in recent decades, the organisation of research and training of specialists at the faculty of history of the Belarusian State University has reached a new interdisciplinary level.